Islamism in the Perception of the Teachers and the Students of Pesantren Mawaridussalam Deli Serdang North Sumatra - Lubis, Dahlia (TEOSOFI: Jurnal Tasawuf dan Pemikiran Islam, 2019)
Many studies on pesantren in Indonesia put more emphasis only on the aspect of pesantren as the oldest Islamic educational institution in the archipelago, instead of any other aspects related to this type of educational institution. Recently, a growing number of studies have shifted their topic into one particular focus, namely radicalism or Islamism in pesantren. This paper aims to examine the responses of pesantren teachers and students to the term Islamism. This study has been conducted at Pesantren Mawaridussalam, an Islamic boarding school located in Batang Kuis village, Deli Serdang, North Sumatra, Indonesia. Specifically, this article elaborates on the responses of teachers and students to the issue of the Islamic state, shariazation (make Islamic law as the law of the state), democracy, and jih?d (a struggle or fight against the enemies of Islam). The findings of this study indicate that the teachers and the students have varied understandings of Islamism. Some argue that the term is close to Islamists, while some others believe that it is identical to Islamists. Despite such understanding, most of the teachers and the students reject the use of violence in fighting for the ideals of Islam.